2005
DOI: 10.1097/01.bot.0000155311.04886.7e
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After Low-Energy Fractures in Patients Aged at Least 45 Years Old

Abstract: There is prolonged risk of premature mortality seen in both proximal femoral and proximal humeral fracture groups in the younger age cohorts, possibly as a result of concomitant medical comorbidities contributing to their premature deaths. Elderly patients sustaining proximal femoral fractures, despite high risk of mortality in the first year after injury, have survival approaching those of the general population in the longer term. Elderly patients who sustain wrist fractures have consistently better survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
76
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 32 publications
13
76
2
Order By: Relevance
“…By contrast to previous studies [4,7], we found that female gender was associated with an increased risk of mortality. When combined with the demonstrated overall increased incidence of fracture in females and the trend toward females sustaining more lowenergy fractures at older ages, this increased mortality in females appears to be consistent.…”
Section: S Proximal Humeral Fracturescontrasting
confidence: 99%
See 1 more Smart Citation
“…By contrast to previous studies [4,7], we found that female gender was associated with an increased risk of mortality. When combined with the demonstrated overall increased incidence of fracture in females and the trend toward females sustaining more lowenergy fractures at older ages, this increased mortality in females appears to be consistent.…”
Section: S Proximal Humeral Fracturescontrasting
confidence: 99%
“…Proximal humeral fractures have an excess mortality beyond that of the normal population, estimated at approximately 10% at 1 year [4][5][6][7]. Epidemiological studies have a defined age >60 years, female gender, recent decline in health, insulindependent diabetes mellitus, infrequent walking and neuromuscular weakness as associated with proximal humeral fractures [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that racial and ethnic minorities are less likely to be insured than whites, in part because their incomes are lower on average [33,38]. We found that even when insured at levels comparable to whites, Hispanic and black patients tended to be less likely to receive autologous blood transfusion for THA and TKA.…”
Section: Discussionmentioning
confidence: 70%
“…We could not find 30-and 90-day mortality rates for pelvic and proximal humeral fractures in the literature. Morin et al [16] and Shortt et al [18] compared morality between different fracture sites, but only for long-term mortality (1 year). Patients who had spinal fractures died earlier (within 30 days after fracture) than patients who had other types of fractures.…”
Section: Discussionmentioning
confidence: 99%